Biofilm formation by Salmonella Typhi and Salmonella Typhimurium on plastic cutting board and its transfer to dragon fruit - Pui, Chai Fung; Wong, Woan Chwen; Chai, Lay Ching; Lee, Hai Yen; Tang, John Yew Huat; Ahmad, Noorlis; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Adhesion of microorganism to food contact surface can become a source of microbial contamination.Enhanced resistances to environmental stresses are exhibited by biofilm producers. In this study, biofilm formation by Salmonella Typhi and Salmonella Typhimurium on plastic cutting board was accessed before the evaluation of the transfer of these two pathogens from plastic cutting board to dragon fruit. By using crystal violet assay, it was found that the adhesion on plastic cutting board by these two pathogens was the greatest at time 12 h. Results showed that Salmonella adhesion is strain-dependent and varied with time. The mean transfer rate from contaminated plastic cutting board to dragon fruit was examined to be 0.79 and 0.72 for Salmonella Typhi and Salmonella Typhimurium, respectively. This indicated that there is a risk of cross-contamination which should be concerned.